2004
DOI: 10.1016/j.rmed.2003.11.010
|View full text |Cite
|
Sign up to set email alerts
|

High intensity physical group training in water—an effective training modality for patients with COPD

Abstract: The aim of this study was to examine the effect of high intensity physical group training in water and on land for patients with COPD with regard to physical capacity and health related quality of life (HRQoL). A controlled, semi-randomised study was conducted where 30 patients were randomised to training either in water or on land. Thirteen patients constituted a control group. Forty-three outpatients, with moderate to severe COPD (27w/16m), from two local hospitals in northern Sweden, were included in the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
104
1
7

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(119 citation statements)
references
References 39 publications
7
104
1
7
Order By: Relevance
“…[21][22][23] A small body of research has examined the physiological effects of exercise in water for people with respiratory diseases. 6,10 Reported benefits need to be assessed in greater depth, but they are supported by the findings of this study.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…[21][22][23] A small body of research has examined the physiological effects of exercise in water for people with respiratory diseases. 6,10 Reported benefits need to be assessed in greater depth, but they are supported by the findings of this study.…”
Section: Discussionsupporting
confidence: 57%
“…[3][4][5] In Sweden, exercise in water has been shown to induce a lower heart rate compared to the same exercise intensity on land. 6 In a number of studies of hydro-therapy in a hospital setting, Kurabayashi and colleagues concluded that exercise in a hot spring-water pool may be useful in COPD. [7][8][9][10] Exercise in water has characteristics that may make it beneficial in the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…Seven (Coppoolse et al, 1999;Kurabayashi et al, 2000;O'Shea, Taylor, & Paratz, 2004;Puente-Maestu, Sanz, Sanz, Cubillo et al, 2000;Puente-Maestu, Sanz, Sanz, Ruiz de Ona et al, 2000;Wadell, Sundelin, Henriksson-Larsen, & Lundgren, 2004;Wijkstra et al, 1995) agreed with the criteria of the American College of Sports Medicine (ACSM) (Garber et al, 2011) for the intervention period and number of sessions varied from eight weeks in the majority on trials to twelve weeks in two trials and from two to four sessions a weeks. Therefore, the number sessions a week were at least between two or four sessions a week.…”
Section: Types Of Exercisesmentioning
confidence: 92%
“…The intensity of the training sessions in five articles (Coppoolse et al, 1999;Puente-Maestu, Sanz, Sanz, Cubillo et al, 2000;Puente-Maestu, Sanz, Sanz, Ruiz de Ona et al, 2000;Wadell, Sundelin, Henriksson-Larsen, & Lundgren, 2004;Wijkstra et al, 1995) showed that the goal is 60-90% of heart rate maximum (HR max ) set by the ACSM for improving aerobic fitness ("American college of sports medicine position stand. exercise and physical activity for older adults,"1998a; "American college of sports medicine position stand.…”
Section: Types Of Exercisesmentioning
confidence: 99%
See 1 more Smart Citation